2012
DOI: 10.1016/j.juro.2012.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urethral Stricture in Women

Abstract: In select women vaginal flap urethroplasty and buccal mucosal graft have high success rates, including 100% at 1 year and 78% at 5 years. Urethral dilation has a 6% success rate. Long-term followup is mandatory. Treatment should be individualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 31 publications
2
56
0
3
Order By: Relevance
“…This can cause a urethral stricture resulting in bladder outlet obstruction. Bladder outlet obstruction occurs in 2–29% of all women [8]. This obstruction presents as weak stream, dribbling, recurrent urinary tract infections, and detrusor overactivity [8].…”
Section: Discussionmentioning
confidence: 99%
“…This can cause a urethral stricture resulting in bladder outlet obstruction. Bladder outlet obstruction occurs in 2–29% of all women [8]. This obstruction presents as weak stream, dribbling, recurrent urinary tract infections, and detrusor overactivity [8].…”
Section: Discussionmentioning
confidence: 99%
“…The index patient is well motivated, and the empirically prescribed CISC frequency of once weekly lessens the cost burden. A recent report with larger series and longer follow-up than that reported by Smith et al described a poorer outcome following urethral dilatation for female urethral stricture [3]; however, the patients in the series did not receive long-term CISC, which may have been responsible for the observed lack of sustained response.…”
Section: Discussionmentioning
confidence: 71%
“…Its diagnosis, though simple, is often overlooked and usually made after difficult urethral catheterizations. Female urethral stricture occurs in 4 to 18% of women with bladder outlet obstruction, and, unlike extensively researched male urethral stricture disease, only limited studies on small series are reported in literature [2,3]. The most common etiologies of female urethral stricture are traumatic urethral injury, iatrogenic urethral injury, and inflammatory urethral disease; its optimal management is still under evaluation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, most of the urethroplasty techniques enjoy a high success rate, albeit with a short follow-up. Blavais et al 8 reported a success rate of 78% at 5 years for vaginal and buccal mucosal graft urethroplasties, whereas Mehrsai et al 9 reported a success rate of 76.5% for buccal mucosal graft urethroplasty after a mean follow-up of 28 months. In another study by Meeks et al ,10 the overall recurrence rate for all reconstructive procedures was reported to be 15.6%.…”
Section: Discussionmentioning
confidence: 99%